Igal dance and kulintangan music in urban spaces the case of the Sama Bajau of Baranggay 704, Dakota, San Andres, Manila - Santamaria, Matthew Constancio Maglana (Musika Jornal, 2015)
The performance traditional igal dance and kulintangan music of the Sama Bajau or Sinama-speaking peoples is associated with the rural setting of kampong ayer or water villages in far-flung islands of the southern Philippines. This paper seeks to illustrate that traditional performances exist where artists of traditional genres reside. Like many other Filipinos of various ethnicities the Sama Bajau have found themselves in the urban spaces of Metropolitan Manila. Part 1 introduces the reader to diversity in Sama Bajau ethno-linguistic identities and performance traditions where at least three labels for traditional dancing -- igal, pansak and iluk -- are used. Part 2 draws attention to the Sama Bajau diaspora in the area of the National Capital Region. In Baranggay 704, San Andres, Manila, many of them have taken up residence and have found employment as vendors, domestic helpers and other service-oriented occupations. Part 3 notes the presence of Sama Bajau traditional kulintangan instrumentalists, albeit the absence of full musical instrument ensembles in communities such as Baranggay 704. Given this diaspora of peoples and skills, the paper concludes with the assertion that traditional music and dance research ought to be conducted in urban spaces such as San Andres, Manila. Traditional performances in these spaces are, however, transformed and mediated by strategies of substitution, modification, innovation and digital solutions which are made necessary by conditions of poverty and scarcity of cultural resources.